Forces of nature : a history of Florida land conservation - Henderson, Clay, 1955- (University Press of Florida, 2022)
"In this comprehensive history of land conservation in Florida, Clay Henderson celebrates the individuals and organizations who made the state a leader in state-funded conservation and land preservation"--